VO2max Level of Women's Futsal Players (UIR Student Activity Unit) - silvia, Elma; Yani , Ahmad; Alficandra, Alficandra (INSPIREE: Indonesian Sport Innovation Review, 2022)
The purpose of the study. The aim of this research is to determine the level (VO2Max) in the UIR Student Activity Unit. Materials and methods. The population in this study were 15 female futsal players at the Riau Islamic University. This study uses a descriptive method, which can be interpreted by describing or describing the current state of the research subject/object based on the facts that appear. the type of research is descriptive in which the variables studied are independent about the VO2 max of female futsal players which is measured by the bleeb test. Results. The average score for the VO2 Max level test for the Women's Futsal Student Activity Unit at the University of Isalam Riau with a score of 22.21%. Judging from the norm of the VO2 Max level, the category is classified as not good. Conclusions. Based on the data analysis that has been carried out, it can be concluded that the VO2 Max level of the Players of the Women's Futsal Student Activity Unit with an average value of 22.21% which is located at the interval of 20.00 – 21.27 with a percentage of 40% in the category of Less Once.